2017
DOI: 10.1139/cjfas-2016-0324
|View full text |Cite
|
Sign up to set email alerts
|

Interactive effects of road salt and leaf litter on wood frog sex ratios and sexual size dimorphism

Abstract: Keyword: metalloestrogen, sex determination, phytoestrogen, sex reversal https://mc06.manuscriptcentral.com/cjfas-pubs Canadian Journal of Fisheries and Aquatic Sciences Interactive effects of road salt and leaf litter on wood frog sex ratios and sexual size dimorphism 1 2 https://mc06.manuscriptcentral.com/cjfas-pubs Canadian Journal of Fisheries and Aquatic Sciences 18 implications for population dynamics. Despite 22 million metric tons of salt applied to US roads 19 annually, with much of it entering aquati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
24
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 32 publications
(26 citation statements)
references
References 32 publications
2
24
0
Order By: Relevance
“…Although Kloas et al did not test statistically for sex biases nor for differential responses among males and females (they analyzed males and females separately for chemical effects, but not sex × chemical interactions), it appears that females emerged later than males in the control treatment, and that this pattern may have been reversed in their estradiol treatment across both replicate studies. Other studies have reported a lack of biases in control treatments, but sexually dimorphic impacts of various compounds on size at metamorphosis and time to metamorphosis .…”
Section: Discussionmentioning
confidence: 96%
See 1 more Smart Citation
“…Although Kloas et al did not test statistically for sex biases nor for differential responses among males and females (they analyzed males and females separately for chemical effects, but not sex × chemical interactions), it appears that females emerged later than males in the control treatment, and that this pattern may have been reversed in their estradiol treatment across both replicate studies. Other studies have reported a lack of biases in control treatments, but sexually dimorphic impacts of various compounds on size at metamorphosis and time to metamorphosis .…”
Section: Discussionmentioning
confidence: 96%
“…However, whether atrazine‐mediated impacts on size at metamorphosis and time metamorphosis are sexually dimorphic remains largely unexplored. Recently, Lambert et al reported that the type of leaf litter input (oak, maple, or no litter input) and road salt input (salt added or not added) interacted to change the degree of size dimorphism between male and female wood frogs, suggesting that sexually dimorphic impacts of EDCs on metamorphosis can occur. Sexually dimorphic impacts, particularly if prevalent and antagonistic across sexes, could potentially explain why effects on timing of metamorphosis are somewhat inconsistent across studies (; but see Rohr and McCoy ).…”
Section: Introductionmentioning
confidence: 99%
“…Recent research shows that sublethal salt concentrations can masculinise wood frog metamorphs (Lambert, Stoler, Smylie, Relyea, & Skelly, 2017). Lambert et al (2017) found that road salt concentration of 867 mg Cl − /L decreased the ratio of females in an experimental population by 10%.…”
Section: Amphibiansmentioning
confidence: 99%
“…Recent research shows that sublethal salt concentrations can masculinise wood frog metamorphs (Lambert, Stoler, Smylie, Relyea, & Skelly, 2017). Lambert et al (2017) found that road salt concentration of 867 mg Cl − /L decreased the ratio of females in an experimental population by 10%. More research is needed on the role road salt plays in determining the sex of amphibians-the ongoing decline of amphibian diversity and abundance might potentially be exacerbated by such sublethal effects.…”
Section: Amphibiansmentioning
confidence: 99%
“…Despite presumptions of genetic sex determination, it is well known that amphibian sexual development can be mediated by environmental conditions during embryonic or larval development (Hayes, ; King, ; Tamschick et al., ; Witschi, ). While recent work has focused on chemical agents (Hayes et al., ; Hermelink et al, ; Lambert, ; Lambert, Giller, Barber, Fitzgerald, & Skelly, ; Lambert, Stoler, Smylie, Relyea, & Skelly, ; Reeder et al., ; Tamschick et al., ), earlier research illustrated that temperature can influence sexual development and even promote sex reversal (Witschi, , , ). Surprisingly, comparatively little work since then has evaluated the relevance and variation of temperature influence on amphibian sexual differentiation.…”
Section: Introductionmentioning
confidence: 99%